The Reciprocal Relationship Between Art and Occupational Therapy Practice - Jennifer Fortuna (Scholarworks @ WMU, 2017)
Susan Burwash, Ph.D., OTR/L, an occupational therapy professor and artist based in Washington State, provided the cover art for the Winter 2017 issue of the Open Journal of Occupational Therapy (OJOT). The featured piece contains Professor Burwash's signature fauxpals, lampwork glass beads made from molten glass and pure silver foil. Art creates balance between traditional medicine and personal medicine, those meaningful activities that give life purpose. Professor Burwash's personal medicine is making beautiful things that can be given away.